THE EFFECT OF INTELLECTUAL CAPITAL ON FINANCIAL PERFORMANCE OF INNOVATIVE MANUFACTURING COMPANIES IN INDONESIA: THE MEDIATING EFFECTS OF COMPETITIVE ADVANTAGE - Andi Wijayanto; Suhadak Suhadak; Moch. Dzulkirom; Nila Firdausi Nuzula (UPT Penerbitan Universitas Jember)
In the era of knowledge economy, Intellectual Capital is an important factor for corporate competitive advantage and higher Financial Performance. This study aims to examine the mediating effect of Competitive Advantage on the influence of Intellectual Capital on Financial Performance. The study was conducted on 31 innovative manufacturing companies listed on the Indonesia Stock Exchange. Innovative manufacturing companies are companies that demonstrate a commitment to conducting research and development activities. The data analyzed was data from 2011-2016. Data analyzed used Generalized Structured Component Analysis (GSCA). The mediating effect of Competitive Advantage was tested used Sobel Test. The result of this research concludes that Intellectual Capital has positive and significant influence on Competitive Advantage, Intellectual Capital has positive and significant influence on Financial Performance, and Competitive Advantage has negative and significant effect on Financial Performance. Competitive Advantage significantly mediates the influence of Intellectual Capital on Financial Performance.